Representative time use data and calibration of the American time use studies 1965 - 1999 - Joachim Merz; Henning Stolze (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2006)
Valid and reliable individual time use data in connection with an appriate set of socio-economic background variables are essential elements of an empirical foundation and evaluation of existing time use theories and for the search of new empirical-based hypotheses about individual behavior. Within the Yale project of Assessing American Heritage Time Use Studies (1965, 1975, 19895, 1992-94 and 1998/99), supported by the Glaser Foundation, and working with these time use studies, it is necessary to be sure about comparable representative data. As it will become evident, there is a serious bias in all of these files concerning demographic characteristics, characteristics which are important for substantive time use research analyses. Our study and new calibration solution will circumvent these biases by delivering a comprehensive demographic adjustment for all incorporated U.S. time use surveys, which is theoretically funded (here by information theory and the minimum information loss principle with its ADJUST program package), is consistent by a simultaneous weighting including hierarchical data, considers substantial requirements for time use research analyses and is similar and thus comparable in the demographic adjustment characteristics for all U.S. time use files to support substantial analyses and allows to disentangle demographic vs. time use behavioral changes and developments. – – Valide und zuverlässige individulle Zeitverwendungsdaten zusammen mit geeigneten sozio-ökonomischen Hintergrundvariablen sind essentiell für eine empirische Fundierung und Evaluierung bestehender Zeitverwendungstheorien and für die Suche nach neuen empirisch fundierten Hypothesen über individuelles Handeln. Innerhalb des Yale Projektes 'Assessing American Heritage Time Use Studies' (1965, 1975, 19895, 1992-94 and 1998/99), das von der Glaser Foundation unterstützt wird, und der Arbeit mit diesen Zeitbudgetdaten ist es notwendig, sich auf die Repräsentativität mit vergleichbarer demographischer Struktur verlassen zu können. Wie ersichtlich wird, gibt es deutliche Abweichungen bei der Repräsentativität demographiacher Charakteristika in allen US Zeitverwendungsstudien, und zwar hinsichtlich demographischer Charakteristika, die bedeutend für die inhaltliche Analyse der Zeitverwendung sind.Unsere Studie und die neue Hochrechnungslösung überwindet diese Verzerrungen mit einer demographischen Hochrechnung, die vergleichbar für alle US Files ist, theoretisch fundiert ist (hier durch die Informationstheorie und dem Minimum Information Loss Prinzip mit dem ADJUST Programmpaket), konsistent durch eine simultane Gewichtung ist, die hierarchische Daten beinhaltet, substantielle Anforderungen der Zeitverwendungsforschung unterstützt und es erlaubt, demographische Veränderungen von Verhaltensänderungen zu trennen.
Keywords: J22; J29; J11; Z0; 330; time use; calibration (adjustment re-weighting) of microdata; information theory; minimum information loss principle; American Heritage Time Use Studies; ADJUST program package; Zeitverwendung; Hochrechung (Umgewichtung) von Mikrodaten; Informationstheorie; Minimum Information Loss Prinzip; American Heritage Time Use Studies; ADJUST Programmpaket; Zeitverwendung; Soziale Lage; USA